A Nontarget Mechanism to Explain Carcinogenesis Following α-Irradiation. Issue 4 (20th December 2019) - Priest, Nicholas D.
This commentary highlights the published data on the metabolic processes that lead to the development of cancer following intakes of asbestos and chemical agents. Following exposure to both, the key initiating event is cell injury leading to cell death that may further lead to inflammation, fibrosis, and cancer. Since α-particle transits also kill cells, it is suggested that cell death and inflammation will also trigger carcinogenesis within tissues irradiated by these particles. Such an explanation would be consistent with the inflammation and fibrosis seen in tumor-bearing tissues irradiated by radon-222, radium-226, thorium-232, plutonium-239, and other α-emitting radionuclides. It would also provide an explanation for dose-related changes in latency and in the similar dose–responses for the same tissue in differently sized species.